2020
DOI: 10.1002/ldr.3631
|View full text |Cite
|
Sign up to set email alerts
|

The features of main osmolytes, silicon and their coupling effects in improving drought resistance of the typical xerophytes in the desert areas of Northwest China

Abstract: Succulent xerophytes (SX) and less succulent xerophytes (LSX) are able to accumulate inorganic ions and synthesize organic solutes (OS) to adapt to drought stress. Silicon (Si) is one of the five beneficial elements for plants and its importance to SX has been confirmed. In the study, the features of main osmolytes and Si were studied in SX and LSX species, and the coupling effects of inorganic ions were investigated in the SX H. ammodendron and LSX C. korshinskii. Results showed that SX and LSX had the common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Interestingly, Haloxylon ammodendron could absorb and accumulate a great quantity of Na + as important osmotica, while still being able to accumulate calcium (Ca 2+ ), magnesium (Mg 2+ ), silicon (Si), etc. to resist to water stress, and the better coupling of these mineral nutrients (Na + , K + , Ca 2+ , Mg 2+ , Si, and N) at suitable level can more effectively improve drought stress of Haloxylon ammodendron than Na or Na compound fertilizer (Kang et al 2013(Kang et al , 2014(Kang et al , 2016a(Kang et al , b, 2017(Kang et al , 2020, indicating that based on the special organic fertilizer, the rational combination of Na + , Ca 2+ , Mg 2+ , and Si accompanied with N and P would contribute to assisting in developing new fertilizers to restore the degraded vegetations in arid areas of northwest China. Studies are worthwhile to further optimize the special organic fertilizer proportion for these succulent xerophyte species grown in barren desert soil.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Haloxylon ammodendron could absorb and accumulate a great quantity of Na + as important osmotica, while still being able to accumulate calcium (Ca 2+ ), magnesium (Mg 2+ ), silicon (Si), etc. to resist to water stress, and the better coupling of these mineral nutrients (Na + , K + , Ca 2+ , Mg 2+ , Si, and N) at suitable level can more effectively improve drought stress of Haloxylon ammodendron than Na or Na compound fertilizer (Kang et al 2013(Kang et al , 2014(Kang et al , 2016a(Kang et al , b, 2017(Kang et al , 2020, indicating that based on the special organic fertilizer, the rational combination of Na + , Ca 2+ , Mg 2+ , and Si accompanied with N and P would contribute to assisting in developing new fertilizers to restore the degraded vegetations in arid areas of northwest China. Studies are worthwhile to further optimize the special organic fertilizer proportion for these succulent xerophyte species grown in barren desert soil.…”
Section: Resultsmentioning
confidence: 99%
“…Drought is a natural disaster caused by insufficient precipitation for a long period of time, with the characteristics of wide influence range, high occurrence frequency, and long duration, making it one of the main climate disasters Cao et al, 2022). In typical arid areas in Northwest China, drought leads to dry land, which directly affects the growth and development of xerophytes (Kang et al, 2020), and it easily causes continuous desertification of land and becomes the source of sandstorms (Yang et al, 2021). Therefore, research on drought in Northwest China has attracted much attention (Luo et al, 2021a;Li et al, 2022;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to absorbing and accumulating Na + as an effective osmotic regulator, desert succulent xerophytes also absorbed and stored Si as an important adaptive way to respond to drought stress (Kang et al, 2014, 2015; Kang et al, 2016). Based on the above research, Kang et al (2020) revealed the accumulation characteristics of Si and other mineral elements (Na, K, Ca, Mg, Si, N, and P) and their coupling effects in drought resistance of desert plants, and then developed mineral fertilizers that could significantly promote the growth and enhance drought resistance of the succulent and less succulent xerophytes. Furthermore, Si absorption and accumulation improved the antioxidant metabolism and osmotic regulation ability of the xerophyte Glycyrrhiza uralensis under drought and salt stress.…”
Section: Introductionmentioning
confidence: 99%